Public policies for the development of sustainable cattle sector with silvo-pastoral systems in Colombia, Argentina, and Costa Rica - Burkart, Stefan; Moreno Lerma, Leonardo; Díaz, Manuel; Triana Ángel, Natalia (International Center for Tropical Agriculture, 2023)
By contributing more than 25% and 10% to the global beef and milk supply, Latin America and the Caribbean plays an important role in the global cattle industry. The cattle sector generates internal and external benefits as it guarantees food security and strongly contributes to economic development. Cattle production in the region not only has a long tradition but also is foreseen a promising future. By 2050, global meat consumption will increase by 100%, favoring the Latin American cattle industry due to its geographic location and availability of both human and natural resources. Despite this positive panorama, traditional cattle systems are still predominant in the region and can cause multiple environmental impacts, such as on water and soil resources, the loss of biodiversity, greenhouse gas (GHG) emissions, and deforestation. The political debate thus centers around the transition from traditional to sustainable cattle systems, in which natural resources are being conserved and social and economic benefits increased. Despite the existence of numerous sustainable production alternatives, such as silvo-pastoral systems (SPS), adoption levels are low and the shift towards sustainability is perceived as slow and uncoordinated.